2021
DOI: 10.3390/microorganisms9061207
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Ecosystems of the Anthropocene: Limnology and Microbial Ecology of Mine Pit Lakes

Abstract: Mine pit lakes (‘pit lakes’) are new aquatic ecosystems of the Anthropocene. Potentially hundreds of meters deep, these lakes are prominent in the landscape and in the public consciousness. However, the ecology of pit lakes is underrepresented in the literature. The broad goal of this research was to determine the environmental drivers of pelagic microbe assemblages in Australian coal pit lakes. The overall experimental design was four lakes sampled three times, top and bottom, in 2019. Instrument chains were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In contrast to acidic pit lakes, non-acidic (pH > 6.5) moderately saline pit lakes are often considered benign environments with low rehabilitation priority. Thus, like natural saline lakes ( Williams, 1996 ), saline pit lakes are under-researched ( Williams, 1996 ; Mori et al, 2019 ; Blanchette and Lund, 2021 ). Similar to acid pit lakes, saline pit lake rehabilitation strategies would focus on water quality improvement or minimization of pit outflows ( Mehanna et al, 2010 ; Mouhamad et al, 2017 ; Nielsen, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to acidic pit lakes, non-acidic (pH > 6.5) moderately saline pit lakes are often considered benign environments with low rehabilitation priority. Thus, like natural saline lakes ( Williams, 1996 ), saline pit lakes are under-researched ( Williams, 1996 ; Mori et al, 2019 ; Blanchette and Lund, 2021 ). Similar to acid pit lakes, saline pit lake rehabilitation strategies would focus on water quality improvement or minimization of pit outflows ( Mehanna et al, 2010 ; Mouhamad et al, 2017 ; Nielsen, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although research on microbial taxonomic diversity in pit lakes has been limited, pit lakes host a diverse microbial community within their waters and sediments ( Blanchette et al, 2020 ; Grettenberger et al, 2020 ; Blanchette and Lund, 2021 ; Xin et al, 2021 ). From our knowledge of other aquatic ecosystems, microbes will play a key role in pit lake ecosystem function through nutrient cycling, the fate and transport of metals and metalloids, mineral formation, biogeochemical processes, decomposition of organic matter, and interactions with other organisms ( Oren, 2004 ; Pace et al, 2016 ; Gupta et al, 2017 ; Flemming and Wuertz, 2019 ; Morris et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity to aquatic and terrestrial animals, groundwater and surface water contamination, salinization, groundwater drawdown, outflow groundwater mixing, drowning risks, and disease reservoirs were initially identified as the main risks of pit lakes (McCullough & Lund, 2006). More recent studies have identified risks such as radioactivity (Manjón et al, 2013; Manjón et al, 2019; Mantero et al, 2020), watercourse “flow‐throughs” (Lund et al, 2018), build‐up of gasses (Boehrer et al, 2016; Sánchez‐España, Yusta, & Boehrer, 2020), and cyanobacterial blooms (Blanchette & Lund, 2021; Goździejewska et al, 2021). Each pit lake is unique, and depending on future use, requires a tailored approach for delivering ecosystem services and community benefits.…”
Section: Risks Of Pit Lakesmentioning
confidence: 99%
“…Pit lakes can increase the diversity of post‐mining landscapes by adding aquatic ecosystems where formerly there were only terrestrial ecosystems (McCullough & van Etten, 2011; Figure 5). Development as aquatic ecosystems is an inevitability for most pit lakes, although the timeframe for this to occur could be great and the ecosystem endpoint is often undefined (Blanchette et al, 2019; Blanchette & Lund, 2021). Small and shallow pit lakes have been successfully closed and rehabilitated or have naturally evolved (Campbell & Lind, 1969; King et al, 1974; Opitz et al, 2020; Stephenson & Castendyk, 2019).…”
Section: Future Uses Of Pit Lakesmentioning
confidence: 99%
“…Since these effects are influenced by microbial community composition, it is necessary to study the link between lacustrine environmental conditions (Lewis, 2009), species distributions and mechanisms of selection (Bryanskaya et al, 2016). Thus, sedDNA surveys are necessary in order to understand microbial community assembly in emergent ecological niches (Mandakovic et al, 2018) and assess environmental resilience as pristine ecosystems transit to human-dominated ecosystems of the Anthropocene (Sun et al, 2017;Blanchette and Lund 2021;Fiskal et al, 2021).…”
Section: Anthropogenic Expansion Of Adaptive and Versatile Ubiquistsmentioning
confidence: 99%